2014
DOI: 10.1158/1541-7786.mcr-13-0503
|View full text |Cite
|
Sign up to set email alerts
|

Cocarcinogenic Effects of Intrahepatic Bile Acid Accumulation in Cholangiocarcinoma Development

Abstract: Bile acid accumulation in liver with cholangiolar neoplastic lesions may occur before cholestasis is clinically detected. Whether this favors intrahepatic cholangiocarcinoma development has been investigated in this study. The E. coli RecA gene promoter was cloned upstream from Luc2 to detect in vitro direct genotoxic ability by activation of SOS genes. This assay demonstrated that bile acids were not able to induce DNA damage. The genotoxic effect of the DNA-damaging agent cisplatin was neither enhanced nor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 35 publications
0
58
0
1
Order By: Relevance
“…Bile salts and bile acids are considered to be potential carcinogens. For example, bile acids play a role in colorectal carcinogenesis through ERKs and PKC signaling pathway (41); intrahepatic bile acid accumulation may have cocarcinogenic effects on the development of cholangiocarcinoma (42). Glycochenodeoxycholate (Glycine conjugate of chenodexycholate) is the main ingredient in the bile.…”
Section: Discussionmentioning
confidence: 99%
“…Bile salts and bile acids are considered to be potential carcinogens. For example, bile acids play a role in colorectal carcinogenesis through ERKs and PKC signaling pathway (41); intrahepatic bile acid accumulation may have cocarcinogenic effects on the development of cholangiocarcinoma (42). Glycochenodeoxycholate (Glycine conjugate of chenodexycholate) is the main ingredient in the bile.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, growth-promoting effects of conjugated bile acids via the activation of sphingosine 1-phosphate receptor 2 have been reported 128,129 . In sum, in experimental models, bile acid accumulation during cholestatic conditions seems to facilitate carcinogenesis via the induction of biliary proliferation and inflammation rather than by direct mutagenic effects 36 .…”
Section: Biliary Compoundsmentioning
confidence: 99%
“…All these risk factors share, as a putative pathogenic mech anism, chronic inflammation involving the biliary tract 34,35 . This process might be favoured by local intrahepatic accumulation of bile acids, even in the absence of net cholestasis 36 . Several toxic and environmental factors are known or suspected to be Nature Reviews | Gastroenterology & Hepatology 1,5,30 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…The physiological concentration or the modest elevation of BA levels, such as in exclusively FXR or SHP individual knockout mice, cannot lead to YAP activation [41] . Consistent with the observation that elevated BA levels in mice fed with a 0.2% cholic acid diet significantly promoted N-nitrosodiethylamine-initiated hepatocellular carcinoma (HCC) [19] formation, Lozano et al [45] revealed that intrahepatic BA accumulation in bile-duct-ligated rats facilitated the carcinogenic effects of thioacetamide metabolites in cholangiocarcinoma development. The persistently high levels of BA enhanced the inflammation and bile duct proliferation, and led to the downregulation of FXR expression.…”
Section: Fxr Bile Acid and Liver Cancermentioning
confidence: 71%
“…The persistently high levels of BA enhanced the inflammation and bile duct proliferation, and led to the downregulation of FXR expression. Those data indicate that during hepatocarcinogenesis, BAs may function as tumor promoters as well as DNA-damaging initiators [19,45] . The imbalanced ratio of free and conjugated BAs also promotes the growth of human cholangiocarcinoma via FXR [46] .…”
Section: Fxr Bile Acid and Liver Cancermentioning
confidence: 87%